Community Empowerment Through Making Iboni Craft to Improve Community Welfare and The Economic Impact - Ari Dwi Setyowati; Amin Yusuf; Abdul Malik; Jingduo Wang (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2023)
The people of Rowoboni Village have not optimized the potential of water hyacinths in Lake Rawapening. People only work as laborers picking water hyacinths and selling raw to collectors. It does not improve the community’s economy because the selling price of water hyacinths is still lower than that of water hyacinths processed into handicraft products. This study aims to describe the process of water hyacinth Iboni craft community empowerment to improve community welfare and economy. This qualitative approach used in-depth interview techniques with 14 participants consisting of one manager, seven workers, four devices village, one farmer, and one hyacinth collector who are considered to have precise information related to the focus of the research. Data collection techniques in this study used observation, interviews, and documentation. Data validity applied source triangulation techniques, and the data were analyzed through data collection, reduction, presentation, and conclusions. The results of this study show that the empowerment process of Iboni craft consists of 3 stages, namely 1) awareness and behavior formation, 2) knowledge and skills transformation, and 3) intellectual and skills enrichment or improvement. The economic impact of this empowerment program is increasing people’s income and welfare. The conclusion is that the empowerment process of Iboni Craft consists of 3 stages:  1) awareness and behavior formation through Dialogical communication or word of mouth to the public, 2) knowledge and skills transformation through group training, and independent training with the manager of Iboni Craft, 3) intellectual and skills enrichment or improvement where the workforce begins to produce independently following consumer demand. The economic impact of this empowerment program is an increase in family income, which can provide the family with a second source of income.